The effects of trunk occlusion in video-based projections on reaction time of elite Silat athletes - Nur Fadzlyn Mohd Zahruddin (Nanyang Technological University, 2021)
The study aimed to investigate the visual-perceptual motor skills (VPMS), specifically reaction time (RT), of elite Silat athletes when responding to varying Silat-specific attacks performed in non-occluded and occluded conditions. It was hypothesised that (i) elite Silat athlete would register longer RT to respond to projected attacks when trunk occlusion was present and (ii) there is a higher number of incorrect responses in occluded condition compared with the non-occluded condition. Eight male elite Silat athletes were recruited. Responses under the two conditions were recorded by a 3D motion analysis system and involved the use of an integrated stereoscopic system. RT was inferred from the mediolateral pelvis movement. No significant difference were found between non-occluded and occluded trunk region conditions with respect to RT. Additionally, the non-occluded condition did not elicit statistically significant difference in incorrect responses when compared to the occluded condition. The ability of the participants to gather adequate visual information from other regions of the body at the initial stage, before the initiation of attack by the virtual opponent, grants quick and precise decision-making which were not affected by occlusion conditions. Future study may consider increasing the demand on hand by increasing the stimulus-response properties through the evaluation according to Hick’s Law. For example, a lateral step followed by a punch could be the appropriate response for a crocodile takedown, whereas a lateral step followed by a back thrust kick would be the appropriate response for an roundhouse kick.